Brega Art and ways to negotiate uncertainties (Palíndromo, 2021)
The present paper aims to point out the motivations of an art historian regarding the challenges this discipline has faced in the past three decades. With an evident autobiographical approach, the text makes conceptual choices, elected notions, and uses brega as a methodological practice to construct approaches to art. We also suggest some epistemological models to understand artistic production, whether by making the authors of the text explicit, or by partnerships of what we call a community of interpreters.
Keywords: Art History; Museological Institutions; Brega; Collections